2011
DOI: 10.1128/aem.02839-10
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Reduction of Salmonella enterica Serotype Typhimurium Viability via Membrane Destabilization following Exposure to Multiple-Hurdle Treatments with Heated, Acidified Organic Acid Salt Solutions

Abstract: The antimicrobial activity of organic acids in combination with nonchemical treatments was evaluated for inactivation of Salmonella enterica serotype Typhimurium within 1 min. It was observed that the effectiveness of the multiple-hurdle treatments was temperature (P < 0.05) and pH (P < 0.05) dependent and corresponded to the degree of organic acid lipophilicity (sodium acetate being least effective and sodium propionate being the most effective). This led to the hypothesis that the loss in viability was due a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…Responses were dependent on the type of acid used and were time dependent, with hilA being upregulated after a 2-h exposure to the respective acid (350). When Milillo et al compared S. Typhimurium transcriptome responses to sodium acetate and sodium propionate exposure after 1 min (55°C at pH 4.0), the respective gene expression patterns were similar, with no increases in expression levels of rpoS, phoPQ, or virulence factors despite their established roles in organic and inorganic acid stress (35,327,328,338). Conversely, genes related to attachment and/or motility functions were induced, which has been observed previously for S. Typhimurium attachment genes after exposure to 42°C (351).…”
Section: Salmonella Virulence Response and Organic Acidsmentioning
confidence: 96%
See 1 more Smart Citation
“…Responses were dependent on the type of acid used and were time dependent, with hilA being upregulated after a 2-h exposure to the respective acid (350). When Milillo et al compared S. Typhimurium transcriptome responses to sodium acetate and sodium propionate exposure after 1 min (55°C at pH 4.0), the respective gene expression patterns were similar, with no increases in expression levels of rpoS, phoPQ, or virulence factors despite their established roles in organic and inorganic acid stress (35,327,328,338). Conversely, genes related to attachment and/or motility functions were induced, which has been observed previously for S. Typhimurium attachment genes after exposure to 42°C (351).…”
Section: Salmonella Virulence Response and Organic Acidsmentioning
confidence: 96%
“…Other stress combinations appear to have more of an impact on SCFA inhibition of Salmonella. Milillo and coworkers demonstrated not only that the combination of heat (50°C to 60°C) and organic acids was more effective than single intervention applications when applied to S. Typhimurium but also that heated acidified solutions caused substantial membrane damage and leakage of intracellular ions (338,339). There may also be potential serovar differences.…”
Section: Salmonella Acid Tolerance Response and Organic Acidsmentioning
confidence: 99%
“…10C). The antidiarrheal drug Lactéol Fort includes a lyophilized heatinactivated culture of L. acidophilus strain LB that contains lactic acid, and a heated and acidified, but not a nonheated, lactic acid solution destabilized membranes and promoted potassium leakage in stationary-phase S. Typhimurium (38). Experiments to determine whether or not the heated (110°C) MRS broth containing lactic acid modified the swimming of exponential-phase S. Typhimurium SL1344 showed that treatment with heated lactic acid at 50 or 100 mM did not modify S. Typhimurium SL1344 motility whereas treatment with a concentration of 200 mM resulted in a 2-fold increase in inhibitory activity compared with nonheated lactic acid results (not shown).…”
Section: Vol 55 2011 L Acidophilus Lb Blocks S Typhimurium Motilimentioning
confidence: 99%
“…The antimicrobial effect of organic acids appears to be the result of lipophilic, undissociated acids permeating the plasma membrane, resulting in cell death (Adams and Hall, 1988;Milillo et al, 2011). PMA treatment prior to real-time PCR allows for distinction of viable from dead cells by binding to DNA of dead cells and preventing amplification of the PCR target sequence.…”
Section: Discussionmentioning
confidence: 98%